1997
DOI: 10.1016/s1074-7613(00)80382-9
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the MAPK Pathway on T Cell Lineage Commitment

Abstract: During development, progenitor thymocytes differentiate into either CD4 or CD8 T cells, and this fate decision depends on the specificity of the T cell antigen receptor (TCR) for MHC class II or class I molecules. Based on the mechanisms of fate specification known for simple metazoan organisms, we sought to determine whether the extracellular signal-related kinases (ERKs) play a role in T cell differentiation and lineage commitment. Using a dominant gain-of-function mutant of the erk2 gene, we show that diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
147
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(160 citation statements)
references
References 60 publications
13
147
0
Order By: Relevance
“…For example, in some systems the platelet-derived growth factor (PDGF) stimulates sustained ERK activity and results in S-phase entry or cell differentiation whereas epidermal growth factor (EGF) stimulates transient ERK activity that does not drive cells in to S-phase and does not promote cell differentiation [204][205][206][207]. Duration and strength dependent modulation of cell fate appear to operate in neuronal PC12 cells, NIH3T3 fibroblasts [208], macrophages [209] and lymphocytes [210,211]. It is becoming apparent that cell fates determined by different growth factors that activate the same MAPK components requires a spatiotemporal control of MAPK targeting, sequestration and activation.…”
Section: Multiple Erk Scaffolds Regulate the Diverse Functions Of Thementioning
confidence: 99%
“…For example, in some systems the platelet-derived growth factor (PDGF) stimulates sustained ERK activity and results in S-phase entry or cell differentiation whereas epidermal growth factor (EGF) stimulates transient ERK activity that does not drive cells in to S-phase and does not promote cell differentiation [204][205][206][207]. Duration and strength dependent modulation of cell fate appear to operate in neuronal PC12 cells, NIH3T3 fibroblasts [208], macrophages [209] and lymphocytes [210,211]. It is becoming apparent that cell fates determined by different growth factors that activate the same MAPK components requires a spatiotemporal control of MAPK targeting, sequestration and activation.…”
Section: Multiple Erk Scaffolds Regulate the Diverse Functions Of Thementioning
confidence: 99%
“…61 Similarly, other studies have suggested that increased or decreased MAPK signaling can influence T cell differentiation between either a CD4 or CD8 expressing cell lineage. 62 In nonleukemic cells, several groups have demonstrated that MAPK signaling can both promote and inhibit adipogenesis and myogenesis in pre-adipocytes and myoblasts, respectively, in a time and context-dependent manner. [63][64][65][66] Thus in some established cell systems, constitutive elevation of MAP kinase activity can stimulate proliferation, whereas in others it triggers increased p21 Cip-1/MDA6/WAF1 levels, cell cycle arrest, and cellular maturation.…”
Section: An Overview For the Role Of The Map Kinase Pathway In Prolifmentioning
confidence: 99%
“…How signals that induce positive selection trigger differentiation into the CD4 ϩ or CD8 ϩ mature cell type is not fully understood. Nonetheless, quantitative differences in MAPK and Lck activation appear to alter the CD4 ϩ / CD8 ϩ differentiation ratio (12,13).…”
mentioning
confidence: 99%